Breaking Chains : Slavery on Trial in the Oregon Territory - Nokes, R. Gregory (Book collections on Project MUSE., 2013)
This book tells the story of the only slavery case ever adjudicated in Oregon courts - Holmes v. Ford. Drawing on the court record of this landmark case, the author offers an intimate account of the relationship between a slave and his master from the slave's point of view. He also explores the experiences of other slaves in early Oregon, examining attitudes toward race and revealing contradictions in the state's history. Oregon was the only free state admitted to the union with a voter-approved constitutional clause banning African Americans and, despite the prohibition against slavery, many in Oregon tolerated it, and supported politicians who were pro-slavery, including Oregon's first territorial governor. -- Summary from book cover.